The Mediating Effects of Diabetes Distress, Anxiety, and Cognitive Fusion on the Association Between Neuroticism and Fear of Hypoglycemia in Patients With Type 2 Diabetes - Huang, Jing; Ding, Shenglan; Xiong, Shuyuan; Liu, Zhiping (Frontiers in Psychology, 2021)
Purpose: To explore the relationship between neuroticism and fear of hypoglycemia (FoH) among patients with type 2 diabetes (T2D), as well as the mediating effects of diabetes distress, anxiety, and cognitive fusion on the relationship between neuroticism and FoH. Methods: A total of 494 patients with T2D (39.9% females, n = 197) were analyzed using the neuroticism scale of the Eysenck Personality Questionnaire-Revised Short Scale (EPQ-RS), the Fear of Hypoglycemia-15 Scale (FH-15), the Diabetes Distress Scale (DDS), the Self-Rating Anxiety Scale (SAS), and the Cognitive Fusion Questionnaire (CFQ). The bootstrapping method was used to test the separate and parallel mediation models. Results: FoH was noted in 17.4% (n = 86) of patients. The correlations between neuroticism, diabetes distress, anxiety, cognitive fusion, and FoH were positive. Diabetes distress, anxiety, and cognitive fusion were significant mediators in the association between neuroticism and FoH in both separate and parallel mediation models. In the parallel mediation model, the mediating effect of anxiety was the highest, and the mediating effect of diabetes distress was the lowest, but no significant differences were found in the comparison of these three indirect effects. Conclusion: This study indicated that neuroticism not only directly affected FoH, but also indirectly influenced FoH via the increase of diabetes distress, anxiety, and cognitive fusion in patients with T2D. The results provide a theoretical basis for the development of intervention programs to ameliorate patients’ FoH directly and indirectly. Healthcare providers should be encouraged to develop appropriate programs based on improving diabetes distress, anxiety, and cognitive fusion to help patients with T2D improve FoH.